2018
DOI: 10.5146/tjpath.2018.01430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic importance of c-myc and bcl-2 expressions and the presence of epstein-barr virus in classical hodgkin lymphoma

Abstract: We could not find any relationship between Bcl-2, c-Myc and EBER-ISH positivity and the low/high IPS groups in cHL. New studies with larger series are needed in which more precise cut-off values are used and clinically and biologically heterogeneous groups of cHL patients are determined more clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…Kilicarslan et al in their study could not find any differences between positive and negative EBV cases in terms of International Prognostic Score (IPS) and bone marrow involvement, but there was significantly high extranodal involvement in those cases which were EBV positive. 27 According to Souza et al the presence of EBV does not change the clinical evolution and overall-survival of patients treated with similar chemotherapy protocols. 28 On contrary, others have found correlation with advanced stage but without significant influence on survival, although in younger patients the progression-free survival was longer.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kilicarslan et al in their study could not find any differences between positive and negative EBV cases in terms of International Prognostic Score (IPS) and bone marrow involvement, but there was significantly high extranodal involvement in those cases which were EBV positive. 27 According to Souza et al the presence of EBV does not change the clinical evolution and overall-survival of patients treated with similar chemotherapy protocols. 28 On contrary, others have found correlation with advanced stage but without significant influence on survival, although in younger patients the progression-free survival was longer.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, the EBV has been determined to be positive in nearly 40% to 50% of cHL patients. 2628 Whether there is a relationship between EBV infection and the advanced clinical stages of cHL is highly debatable. Kilicarslan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoplasmic reticulum stress associated with the viral infection has been shown to be involved in the pathogenesis of HL ( 11 ). In addition, it has been reported that positivity of EBER-ISH is associated with a high frequency of extranodal involvement in patients with CHL ( 12 ). Reed-Sternberg cells and Hodgkin cells with a rich inflammatory background ensure their survival through the selective recruitment of cells in their microenvironment, constitutional activation of anti-apoptotic pathways, and elaborate evasion of the host immune system ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Folglich ist der niedrige Anteil positiver Fälle bei diesen Entitäten am ehesten auf den für die Auswertung verwendeten cut-off von 10% positiv gefärbter Zellen zurückzuführen. Dagegen waren MZL, MM und HL generell seltener positiv gefärbt als in entsprechenden Publikationen (Benharroch et al 1995;Gang et al 2013;Kodali et al 2015;Huang et al 2014;Kiliçarslan et al 2018). Anders als die hochmalignen Entitäten zeigten niedrig maligne Lymphome meist keine homogene MYC-Expression.…”
Section: Bcl2 Bcl6 Mycunclassified